Morphometric Analysis of Gastropods in Jenggalu Mangrove Forest Tourist Park, Bengkulu Province - Zuhepti Despiora; Mega Sari Apriniarti; Pariyanto (ISEJ : Indonesian Science Education Journal, 2026)
Gastropods are a group of mollusks that play an important role in the mangrove ecosystem as detritivores and part of the food chain. The presence and variation of gastropod body shape can be studied through a morphometric approach to determine the growth patterns and morphological characteristics of each species. This study aims to analyze the morphometrics of gastropods found in the Jenggalu Mangrove Forest Tourism Park, Bengkulu City and identify the types of gastropods found in the area. The method used in this study was the Visual Survey (VES) combined with the line transect method. Sampling was carried out directly using hand-picking techniques in the mangrove zone during tidal conditions. Morphometric measurements included shell diameter, shell length, shell height, opening height, spiral height, opening width, and shell weight using calipers and digital scales. The results showed that 8 species of gastropods from 7 families were found with a total of 46 individuals. The most common species found was Littoraria scabra. The relationship between shell length and weight showed a negative allometric growth pattern, where the increase in length was faster than the increase in weight. Based on the research results, it can be concluded that gastropods in the Jenggalu Mangrove Forest Tourism Park area have species diversity and morphometric variations that are influenced by the environmental conditions of the mangrove habitat.